Identification and Isolation of Biosurfactant Producing Bacteria from Oil Spill Contaminated Soil of Ennore: Life Sciences-Microbiology - Vijayanand, Madhumitha; Arul, Arthi; J Ramalingam, Aishwarya; Rajasundaram, Archana (International Journal of Life Science and Pharma Research, 2022)
The bacteria were isolated from the soil samples that were collected in oil spill-contaminated sites located at Kamarajar port in Ennore, Chennai, Tamil Nadu, India. The main aim of this study was to isolate the bacteria that produce biosurfactants from the oil spill contaminated soil in Ennore, Chennai and to produce a growth medium for the bacteria to enrich the growth of the bacteria. For the growth of bacteria, Minimal Medium (MM) and Mineral Salt Medium (MSM) were the two types of growth enrichment medium used and serial dilutions of the bacterial cultures were done for the production of colonies. The objective of the study was to perform tests to identify whether the bacteria can be able to produce the bio-surfactant or not. Tests like Drop collapse method and oil displacement method were done to check for the production of biosurfactant. The bacteria which produce the surface active substances were the one which produces the bio-surfactant. As a result, gram staining was done for identifying the nature of bacteria. Most of the gram positive bacteria are known to have the properties of bio-surfactant. These bacteria has peptidoglycan outer layer that are easier to kill - their thick peptidoglycan layer which absorbs antibiotics and cleaning products easily. Hereby we conclude that the bacteria which produces the biosurfactant is Bacillus and further studies should be done on identifying the bacteria at the species level. Therefore, this study was done to eradicate the oil spill contaminated areas with the help of bacteria in a natural way without harming the environment. Bacillus sp. is a gram-positive bacteria which helps in, liver and renal function, and act as an inflammatory markers and in maintaining blood glucose levels. It does not have an outer cell wall and only has a membrane of peptidoglycan which makes the Bacillus more absorbent and eco-friendly.